Invasive plant species thresholds in the forests of Robinson Crusoe Island, Chile - Vargas-Gaete, Rodrigo; Salas-Eljatib, Christian; Gaertner, Stefanie M.; Vidal Ojeda, Osvaldo Javier; Bannister, Jan R.; Pauchard, Anibal (My University, 2018)
Background: Invasion by exotic plants worldwide can lead to the loss of native species, particularly on islands with a high proportion of endemic plants, such as Robinson Crusoe Island (RCI). Aims: We studied the two most invasive exotic plant species occurring in the forest of RCI: Aristotelia chilensis and Rubus ulmifolius. We aimed at establishing thresholds for environmental and microsite variables related to invasion. Methods: Environmental and forest understorey variables, including canopy gaps and invasive species cover were measured in non-invaded and invaded forest sites. We expected more invasion in plots located close to invasive shrublands, and in large gaps with high solar radiation. Results: We found no relationship between the distance to invasive shrublands and invasion probability. Solar radiation tended to be slightly related with a higher cover of R. ulmifolius, the most abundant invasive exotic plant in RCI forests. Overall, the cover of native ferns appeared to inhibit invasion. Conclusions: The identification of variable thresholds related to invasion can be useful for guiding management decisions. Our results suggest that management should consider monitoring forest canopy gap formation and promote the establishment of ferns to reduce the probability of invasive species establishing.
Keywords: aristotelia; canopy gaps; juan fernández islands; regression trees; restoration; rubus